2017
DOI: 10.1002/ca.23015
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of genital reaffirmation surgery (male‐to‐female): Vaginoplasty using penile skin graft with scrotal flaps

Abstract: Gender reaffirmation surgery is the final step in an individual's transition to their preferred gender. A clear understanding of the anatomy pertinent to this procedure is essential by the surgeon and patient. In male-to-female transgenders, female genitalia is constructed using the individual's penile skin to form the neovaginal canal and their scrotal skin folds post orchiectomy to create the labia majora. The surgical precursors of the remaining anatomical structures of the female genitalia are as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Pauls () reported that the clitoris has an intricate anatomy; therefore, understanding the clitoral frenulum as the anatomical structure stabilizing the clitoris is important, since the clitoris is considered to be central to female orgasmic responses. Saylor et al () emphasized the need for a clear understanding of female anatomy when male‐to‐female transgender surgery is performed. The surgical precursors of the anatomical structures of the female genitalia were itemized by Saylor et al () as follows: the clitoris is crafted from the glans penis so it retains its innervation; the labia minora are formed using excess penile skin tissue; and the long male urethra is shortened to that of its feminine counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pauls () reported that the clitoris has an intricate anatomy; therefore, understanding the clitoral frenulum as the anatomical structure stabilizing the clitoris is important, since the clitoris is considered to be central to female orgasmic responses. Saylor et al () emphasized the need for a clear understanding of female anatomy when male‐to‐female transgender surgery is performed. The surgical precursors of the anatomical structures of the female genitalia were itemized by Saylor et al () as follows: the clitoris is crafted from the glans penis so it retains its innervation; the labia minora are formed using excess penile skin tissue; and the long male urethra is shortened to that of its feminine counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Saylor et al () emphasized the need for a clear understanding of female anatomy when male‐to‐female transgender surgery is performed. The surgical precursors of the anatomical structures of the female genitalia were itemized by Saylor et al () as follows: the clitoris is crafted from the glans penis so it retains its innervation; the labia minora are formed using excess penile skin tissue; and the long male urethra is shortened to that of its feminine counterpart. The main goal of these reconstructive methods is to create a functionally and esthetically acceptable vagina and vulva, together with expected voiding function and satisfactory sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Other less-invasive methods have been proposed, including Creatsas vaginoplasty (modified Williams method) [22], the labial and vestibular flap method [23], and the use of a small graft of perineal skin at the introitus to line the distal posterior aspect of the newly created vagina [24, 25]. In gender reassignment surgery, the most commonly used method is penile inversion vaginoplasty with scrotal flaps [26], sometimes combined with autologous buccal micro-mucosa free grafts [27]. However, several techniques have been attempted to cover (and epithelize) the newly formed vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of South Asian Federation of Obstetrics and Gynaecology, Volume 14 Issue 3 (May-June 2022) cultured vaginal tissue, 12 and labial or gracilis flaps [13][14][15][16] have all been used for the McIndoe procedure.…”
Section: Autologous In Vitromentioning
confidence: 99%